2012
DOI: 10.1097/brs.0b013e31824fffde
|View full text |Cite
|
Sign up to set email alerts
|

Major Complications and Comparison Between 3-Column Osteotomy Techniques in 105 Consecutive Spinal Deformity Procedures

Abstract: Major complications occurred in 35% of 3-column osteotomies and at similar rates for both PSO (38%) and VCR (22%) procedures. The presence of a major complication did not affect the ultimate clinical outcomes at 2 years or more.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
168
4
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(193 citation statements)
references
References 28 publications
6
168
4
10
Order By: Relevance
“…20 Studies have documented the complications that arise, assessing the rates of reoperation, analyzing factors that increase the likelihood of reoperation, and suggesting methods to prevent the need for reoperation. These studies not only reported complications following primary spine surgery 3,8 but also compared complication rates between different types of spine surgeries 14,15 and between primary and revision procedures. 6,11,12 Rates of reoperation are frequently cited, ranging from 10% to 25%, and among the many reasons behind reoperation-including infection, curve progression, proximal junction kyphosis, implant failure, and removal of painful implants 4,13,17 -pseudarthrosis emerges as one of the most commonly documented indications.…”
mentioning
confidence: 99%
“…20 Studies have documented the complications that arise, assessing the rates of reoperation, analyzing factors that increase the likelihood of reoperation, and suggesting methods to prevent the need for reoperation. These studies not only reported complications following primary spine surgery 3,8 but also compared complication rates between different types of spine surgeries 14,15 and between primary and revision procedures. 6,11,12 Rates of reoperation are frequently cited, ranging from 10% to 25%, and among the many reasons behind reoperation-including infection, curve progression, proximal junction kyphosis, implant failure, and removal of painful implants 4,13,17 -pseudarthrosis emerges as one of the most commonly documented indications.…”
mentioning
confidence: 99%
“…Despite variations in techniques, 3COs are effective procedures that allow for the correction of spinal deformity and the restoration of global alignment. 2,4,9,10,26,27 While 3CO procedures are powerful tools in the surgeon's armamentarium for the treatment of spinal deformity, the complexity of these procedures can result in major complications. Analysis of the Scoliosis Research Society morbidity and mortality database showed that patients who underwent osteotomies had higher rates of complications than those who underwent other surgical approaches, and more aggressive osteotomies were associated with higher complication rates.…”
mentioning
confidence: 99%
“…20,25 The complication rate for patients undergoing 3CO surgery has been reported to be up to 59%. 2,13,16,17,27 Risk factors for developing major complications have been identified as advanced age, sagittal deformity, preoperative kyphosis, long fusion constructs, 3 or more medical comorbidities, excessive blood loss, and revision surgery. 2,[6][7][8]11,13 While the incidence and risk factors for complications after 3CO have been defined, these definitions have come from primarily single-center studies with small patient populations.…”
mentioning
confidence: 99%
“…1A), and long-segment fusions are associated with complication rates ranging from 10% to 75%. 4,8,10,11,15,19,23,25,30,31,33 Minimally invasive surgery (MIS) for ASD correction has become increasingly popular. As reported by Smith et al, outcome measures after ASD surgery in elderly patients improve more dramatically than in younger patients, and with an increasing elderly population, minimally invasive surgical correction will remain an important option.…”
mentioning
confidence: 99%